2017
DOI: 10.1097/gox.0000000000001304
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Human Keloids in Mouse Skin

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…The percentage induction of keloid tumors in the murine xenograft model of the present study is consistent with that of other workers [21,[41][42][43][44][45][46]. Our results showed that AKCs administered with hydroxyapatite (HA) produced 100% of keloid tumors in SCID mice and HNA staining confirmed that the tumors were indeed those of human origin.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage induction of keloid tumors in the murine xenograft model of the present study is consistent with that of other workers [21,[41][42][43][44][45][46]. Our results showed that AKCs administered with hydroxyapatite (HA) produced 100% of keloid tumors in SCID mice and HNA staining confirmed that the tumors were indeed those of human origin.…”
Section: Discussionsupporting
confidence: 92%
“…38 Furthermore, prolonged presence of increased levels of type III collagen is indicative of white or keloid scarring. 39 The similarity in color ratios in both treatment and normal areas, along with the evident thinner collagen fibers, indicate that neocollagenesis, as opposed to scarring, is occurring. Increased vascularity with inflammatory infiltrates suggests active neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…4 Existing models have succeeded in inducing hypertrophic (but not keloid) scar in wild-type 5 and immune-deficient mice, 6 rabbits 7 and red duroc pigs, 8 but although similar in appearance to keloids, they don't grow beyond the wound boundary. Other models use implantation of human keloid scar 9,10 or tissue-engineered keloid cells [11][12][13][14] on immune-deficient mice. While these models have found success in replicating a 'keloid-like' wound that grows beyond the wound boundary, there are inherent issues.…”
mentioning
confidence: 99%